Répartition biostratigraphique des orbitolinidés dans la biozonation à ammonites (plate-forme urgonienne du Sud-Est de la France). Partie 1 : Hauterivien supérieur - Barrémien basal [Biostratigraphic distribution of orbitolinids in the ammonite biozones (Urgonian platform of southeastern France). Part 1: Upper Hauterivian-lowermost Barremian] - Clavel Bernard; Busnardo Robert; Charollais Jean; Conrad Marc; Granier Bruno (Carnets de Géologie, 2010)
The proposed biostratigraphic distribution of orbitolinids from the Upper Hauterivian and the lowermost Barremian of SE France is correlated with the ammonite biozonation. It is based on the detailed study of eight sections which delivered orbitolinids intercalated with or capped by levels with ammonites and, in some cases, echinids and dasycladales. Among the 24 species of orbitolinids present during that period, 3 are restricted to the Late Hauterivian: Praedictyorbitolina busnardoi, Paleodictyoconus beckerae and Valserina primitiva.